Patent Protection, Technical Efficiency and Productivity Growth in Indian Manufacturing Industries - Chakravarty Mukherjee, Tanusree (Curtin University, 2021)
This thesis analyses the effect of patent reforms on firm-level technical efficiency and productivity growth in selected Indian manufacturing industries by computing and decomposing productivity changes. The empirical results demonstrate a mixed effect on the components of TFP across the four sunrise industries. It decomposes inefficiency into persistent and transient technical inefficiencies. Two industries experience persistent technical inefficiencies. The mixed impact of the firm-specific variables identifies the significance of specific policies for the different industries.